2005
DOI: 10.1162/0898929055002454
|View full text |Cite
|
Sign up to set email alerts
|

Biases in Attentional Orientation and Magnitude Estimation Explain Crossover: Neglect is a Disorder of Both

Abstract: Crossover refers to a pattern of performance on the line bisection test in which short lines are bisected on the side opposite the true center of long lines. Although most patients with spatial neglect demonstrate crossover, contemporary theories of neglect cannot explain it. In contrast, we show that blending the psychophysical construct of magnitude estimation with neglect theory not only explains crossover, but also addresses a quantitative feature of neglect that is independent of spatial deficits. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
38
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 69 publications
8
38
1
Order By: Relevance
“…Specifically, the bias of attention toward the upper hemispace caused by activation of the ventral system (Drain & ReuterLorenz, 1996;Previc, 1990) should be reversed to a bias toward the lower hemispace by the overestimation of length for very short lines. Figure 3 clearly shows no evidence of a downward bias for the very short lines-contradicting the theory proposed by Mennemeier et al (2005).…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…Specifically, the bias of attention toward the upper hemispace caused by activation of the ventral system (Drain & ReuterLorenz, 1996;Previc, 1990) should be reversed to a bias toward the lower hemispace by the overestimation of length for very short lines. Figure 3 clearly shows no evidence of a downward bias for the very short lines-contradicting the theory proposed by Mennemeier et al (2005).…”
Section: Discussionmentioning
confidence: 51%
“…For example, Mennemeier et al (2005) suggested that crossover occurs because of the interplay between two separate processes: (1) magnitude estimation and (2) orientation bias. Magnitude estimation refers to a phenomenon whereby the length of short lines is systematically overestimated, whereas the length of long lines is underestimated (Tegner & Levander, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations